FOOD AS CULTURE: INFLUENCE OF COLONIALISM ON THE KOCHI CUISINE - Geetha P C (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores the cultural transformation of Kochi’s cuisine under European colonial rule, focusing on the influence of Portuguese, Dutch, and British food practices. Employing a culinary historiographic method, the study integrates archival sources, oral traditions, and ingredient-origin mapping to trace how colonial encounters reshaped local food identities. It highlights the introduction of New World crops like chilli, tomato, and cashew by the Portuguese, the Dutch legacy of baked goods like breudher, and the British integration of bread, tea, and Anglo-Indian curries into Kochi’s urban diet. The study introduces the "Gastro-Colonial Fusion Index" (GCFI) as a novel metric to quantify the extent of cultural blending in key Kochi dishes. Findings underscore food as a living archive of colonial interactions, revealing both culinary enrichment and socio-economic divides. The paper positions Kochi as a gastronomic palimpsest where colonialism continues to flavor local identity.